Warrant Pro 1: Market Price Synthesis with a Software Agent and a Neurosimulator - Patrick Bartels; Michael H. Breitner (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
Todays derivative pricing base on stochastic models developed in the 70s. These models base on some unrealistic assumptions. The system Warrant Pro 1 presented here combines the software agent PISA (Partially Intelligent Software Agent) and the neurosimulator FAUN (Fast Approximation with Universal Neural Networks) to synthesize market price functions instead of theoretical price functions. PISA automatically extracts data from the internet or other (semi-)structured text sources. High quality neural networks training and validation data with predefinable denseness are provided cost ree. FAUN learns true market price functions and computes real market prices. An example for German DAX options is outlined.
Keywords: G13; F31; C80; M19; 330; Market prices; software agent; artificial neural networks; neurosimulator; derivatives